Knowledge and Perception of Emergency Contraception of Women in Shahrekord-Iran - Masoumeh Delaram (Tehran University of Medical Sciences, 2008)
Objective: The aim of this study was to determine knowledge and attitude about emergency contraception among women using condom, coitus interruptus and rhythm methods. Materials and methods: Between April and September 2006, 400 women referring to the health centers in Shahrekord, were evaluated. They entered the study if they were using condom, coitus interruptus or rhythm methods. A questionnaire including demographic information, contraceptive method in use, and patients' awareness and attitude/practice about emergency contraception was completed for each participant. Results: Of the 400 responders, 60.5% were using condom, 38.7% were using coitus interruptus and 0.8% were practicing rhythm method. The awareness was inadequate in 22.5% of women, moderate in 55% and adequate in 22% of them. The attitude of users was positive in more than 70% of them and only 20.5% of women had practiced emergency contraception. The relation of age and job with awareness was significant (P<0.001). A significant relation was considered between the level of education and knowledge of women (P<0.01). The women who had adequate knowledge had practiced the emergency contraception better than those with inadequate knowledge (P<0.001). However, only 27.1% of responders who reported knowing about emergency contraception knew the correct time frame in which emergency contraceptives must be used. Conclusion: There is a critical need to train the women about emergency contraception, emphasizing available methods and correct timing.